CAMBODIAN EFL STUDENTS' INVESTMENT IN LEARNING ENGLISH: PERSPECTIVES AND PRACTICES - Chan, Hum (TEFLIN Journal, 2018)
This article reports on a case study that explored the perspectives and practices of Cambodian EFL students regarding their investment in learning English at the University of Battambang (UBB), Cambodia. The study specifically investigated how the students perceived the role that learning English played in their lives. The study also examined community practices surrounding the learning of English amongst these Cambodian university students. A mixed method approach was employed to collect data in two stages. First, a survey was administered to a random selection of 80 university students. Then, four intensive group interviews were undertaken with a total of 20 students purposively selected through a theoretical sampling. Quan- titative data from the survey was computerized and analyzed using SPSS while the qualitative data obtained from the intensive interviews was coded and interpreted to compare its similarities and differences with statistical data for generating theory. Findings of the study indicate that English has empowered Cambodian learners' perspectives to invest in EFL study as a means for improving their quality of life, gaining better positions, and advancing their salary and social status, which may, in turn, affect their identities and capital.